1967
DOI: 10.1017/s0022172400045939
|View full text |Cite
|
Sign up to set email alerts
|

The examination of samples infected with multiple salmonella serotypes

Abstract: Attention is drawn to the confused epidemiological picture experienced in investigating outbreaks of salmonellosis due to multiple serotypes. Public Health Laboratories are often faced with the examination of specimens containing several serotypes and in this paper six techniques are described which have been found useful in dealing with this problem. The choice of technique depends on the time available for the examination and the epidemiological importance of obtaining an accurate result. A preference is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Some possibilities include serotyping multiple isolates per plate, use of multiple enrichment broths and plating media, culturing multiple samples per pig, or sampling more animals per herd or studied groups. Research on the dynamics of bacterial growth in selective enrichment broths 2,7,8 suggests that selective enrichment may result in asynchronous growth curves among serotypes, because of differing susceptibilities to the restrictive components of the media, with a consequent difference in recovery rates of different serotypes, as demonstrated in our study. Therefore, if only 1 culture method is used, selection of more than 1 colony per sample for identification or sampling more animals per group may not be as efficient as using multiple methods for isolation of different serotypes.…”
supporting
confidence: 64%
“…Some possibilities include serotyping multiple isolates per plate, use of multiple enrichment broths and plating media, culturing multiple samples per pig, or sampling more animals per herd or studied groups. Research on the dynamics of bacterial growth in selective enrichment broths 2,7,8 suggests that selective enrichment may result in asynchronous growth curves among serotypes, because of differing susceptibilities to the restrictive components of the media, with a consequent difference in recovery rates of different serotypes, as demonstrated in our study. Therefore, if only 1 culture method is used, selection of more than 1 colony per sample for identification or sampling more animals per group may not be as efficient as using multiple methods for isolation of different serotypes.…”
supporting
confidence: 64%
“…When examining samples containing multiple salmonella serotypes, use of complementary cultural techniques has been briefly discussed (Harvey, 1957;Harvey & Price, 1967). The present communication records results obtained with two different enrichment broths in routine practice.…”
Section: Introductionmentioning
confidence: 99%
“…From a different point of view, several investigators have reported that a secondary enrichment in selenite broth or tetrathionate broth also tends to increase the yield of salmonellas from food or highly contaminated material (Jameson, 1962(Jameson, , 1963Edel & Kampelmacher, 1968;Martin & Ewing, 1967;Harvey & Price, 1967;and others). In this paper, we report our findings from a comparative evaluation of the isolation of salmonellas from abattoir drains by three different procedures: first, by the use of conventional enrichment media incubated at 370 C.; secondly, by conventional enrichment media incubated at 43°C.…”
Section: Introductionmentioning
confidence: 99%